Larangan Pernikahan Ngalur Ngulon Menurut Perspektif Hukum Islam : Studi Kasus Pengadilan Agama Stabat No 157/ Pdt.P/2023 - Muhammad Habib Hilmy Dahri; Azhar Azhar; Syahrul Affan (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The guardian of marriage in marriage is a pillar that must be fulfilled for the prospective bride who acts to marry her off, without a guardian the marriage is invalid. therefore this case asks the religious court to determine the judge's guardian in order to marry off the bride who is constrained by the guardian adhal because of the involvement of the Ngalur Ngulon custom that is believed by the local community. This research uses a qualitative method with a case study approach. The qualitative approach was chosen because this research aims to understand complex social and legal phenomena related to the Ngalur Ngulon custom and its interaction with Islamic law and state law. the research location chosen by the author is at the Stabat Class-I B Religious Court. This research uses two types of data, primary data and secondary data. In the decision of case number 157/Pdt.P/2023, the Religious Court determines the wali hakim as the marriage guardian of a woman whose nasab guardian is adhal based on Regulation of the Minister of Religion No. 2 of 1987 concerning wali hakim, Law No. 1 of 1974 concerning Marriage, Regulation of the Minister of Religion No. 2 of 1987 concerning Wali Hakim, Regulation of the Minister of Religion 2 of 1987 concerning Guardian Judges, Regulation of the Minister of Religious Affairs No. 30 of 2005 concerning Guardian Judges, Regulation of the Minister of Religious Affairs No. 11 of 2007 concerning Marriage Registration and the Compilation of Islamic Law (KHI) in force based on a presidential instruction in 1991. In Islamic law, there is no prohibition or rule regarding the direction of the house or the location of the bride and groom's house, The important thing is to fulfill the legal requirements of marriage as mentioned earlier (a valid marriage contract, a guardian, a dowry, and witnesses).